Theoretical Calculations about the Nitro-Substituted Derivatives of Indole as Potential High-Energy-Density Compounds. (28th May 2022) - Li, Butong; Li, Lulin; Zhu, Junjie
Abstract: Nitro-substituted derivatives of indole were designed by substituting the hydrogen atoms of indole one by one. To explore the thermal stability, the heats of formation were calculated by using the isodesmic reaction and positive values are confirmed for all of them, which indicated their energetic nature. To explore the kinetic stability, the bond dissociation energies are calculated accompanied by the bond orders, and enough kinetic stability is evaluated. To detect the potential application as high-energy-density compounds, the detonation velocity ( D ), the detonation pressure ( P ), the explosive heats ( Q ), and the molecular density ( ρ ) is calculated further according to the famous Kamlet-Jacobs equation. Based on our calculation, hex-substituted indole has excellent detonation characters ( D = 8.80 km/s, P = 35.88 GPa) and can be regarded as high-energy-density compounds for further research.